Improved Dynamic Response of Buck Converter using Fuzzy Controller - Nagulapati Kiran; Ch Varaha Narasimha Raja (Institute of Advanced Engineering and Science, 2014)
This paper presents comparative performance of Buck Converter in both open as well as closed loop. With the help state equations Mathematical Model of Buck Converter is designed in MATLAB/SIMULINK. The obtained output response of open loop Buck Converter is sluggish, not optimum and consists of peak overshoots. PI Controller is used in closed loop model of Buck Converter. Output Voltage is compared with a reference signal, which then is processed through a controller (PI/Fuzzy). The obtained signal is superimposed with a carrier signal and given to switching device used. To further optimize the performance of Buck Converter and eliminate the peak overshoot present in output response, Fuzzy controller is used. Here Suguno type Fuzzy is used.